Clinical and pedagogical school of Semen Semenovich Zimnitsky - V. N. Oslopov; N. R. Khasanov; Yu. V. Oslopova; E. V. Khazova; Yu. S. Mishanina; D. V. Oslopova (Кардиоваскулярная терапия и профилактика, 2023)
The clinical and pedagogical school of Semyon Semyonovich Zimnitsky is described in close connection with the evolution of his academic status, changes in clinical bases and the social structure of society at the beginning of the 20th century. S. S. Zimnitsky took part in the creation of the Clinical Institute, opened the department of infectious diseases, founded the department of propaedeutics of internal diseases at Kazan State University. The outstanding talent of the lecturer and deep knowledge of clinical material won the love of affection and junior doctors. S. S. Zimnitsky creates methods for teaching therapy at the patient bedside in practical classes and in a lecture course, has an active professional position and is fighting with unreconstructed university professors.